PENGARUH TOTAL ASET DAN FINANCING TO DEPOSITO RATIO (FDR) TERHADAP EMBIAYAAN BANK UMUM SYARIAH DI INDONESIA PRIODE 2015-2019 - Mohamad, Iskandar Fadly; Any, Widayatsari; Rahmat Richard, Rahmat Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of Total Assets and Financing to Deposit Ratio (FDR) on financing at Islamic commercial banks in Indonesia. This study uses secondary data from BUS sharia financial reports published by the Financial Services Authority (OJK) in the form of quarterly from January 2015 to December 2019. The method used in this study is to use the classical assumption test method, multiple linear regression analysis and using the test t or partial test and F test or simultaneous test. The results showed that the variable Total Assets and Financing to Deposit Ratio (FDR) affected the financing where the Sig value on the Total Assets and FDR variables was 0.011 and 0.000 <0.05 and had a tcount of 2.844 and 4.601> ttable of 2.1098 where partially a positive and significant effect on financing. While simultaneously all variables have a sig value of 0,000 where sig value <0.05 and Fcount value of 177.882 where> Ftable value of 3.59, meaning that together the variable total assets and FDR significantly influence the Financing of Sharia Commercial Banks in Indonesia .Keywords: Total Assets, Financing to Deposit Ratio (FDR), Financing